Kepercayaan dan Komunikasi Bermediasi Komputer(Studi Deskriptif Kualitatif Kepercayaan pada Pelaku Personal E-commerce di Aplikasi Chat LINE pada Mahasiswa Prodi Informatika Universitas Muhammadiyah Surakarta) - Alfatoni, Alfatoni; , Palupi, M.A (2017)
E-commerce is the buying and selling practices which do not require to meet physically. E-commerce transactions is a challenge to cultivate trust to potential customer. The purpose of this study is to decribe how trust Informatics Study Program Student Muhammadiyah University of Surakarta force in 2012 to 2015 against the person of personalized the e-commerce on LINE chat applications. This research used descriptive qualitative method. The subject of this research is the studies Informatics Program Student Muhammadiyah University of Surakarta force in 2012 to 2015. Data were collected by semi-structured interview technique. Data analysis method used was triangulation data. The results of research in the trust e-commerce on LINE chat application made by the researchers showed that the trust can be woken up with the ability, benevolence, and integrity of the e-commerce.Abilityinclude product information that should be known by the e-commerce. While benevolence includes the friendliness and service that will be provided by the e-commerce. And integrity that includes background and management of the e-commerce.